Antimicrobial Activity of Essential Oils of Medicinal and Aromatic Plants of the North East India: A Biodiversity Hot Spot. Issue 1 (2nd January 2019) - Munda, Sunita; Dutta, Sukriti; Pandey, Sudin Kumar; Sarma, Neelav; Lal, Mohan
Abstract: The objective of this study was to investigate the antimicrobial activities of essential oil obtained from medicinal and aromatic plants found in Northeastern region of India namely, Cymbopogon flexuosus, Pogostemon cablin, Curcuma caesia, Cymbopogon winterianus, Clausena heptaphylla, Cinnamomum tamala, Psidium guajava, Ocimum sanctum, Cinnamomum camphora and one rhizome Kaempferia galanga . The oils were analyzed by GC and GC/MS. The plant species have good oil yielding capacity of more than 0.50%. The antimicrobial activities were performed against five pathogenic bacteria and four fungal strains. In disc diffusion method, the highest antibacterial activity for all the tested bacteria was shown by Ocimum sanctum oil while Cinnamomum camphora and Psidium guajava oil showed no inhibition except for E. coli and S. aureus respectively . Again the highest antifungal efficiency was shown by Cymbopogon flexuosus oil against the tested microorganisms while the inhibition was negligible for Psidium guajava and Cinnamomum camphora oil . MIC test was performed to confirm the results. Till date very scanty information is available on the plants under study; therefore an effort was made to find out efficacy and effectiveness of different essential oils on different pathogenic strains thereby playing an important role as disinfectant, preservatives in food industry or substitute for synthetic antimicrobial drugs in pharmaceuticals.